Exploring the Role and Impact of Strategic Management Accounting Tools: A Comprehensive Literature Review - Shah, Binod; Sah, Rajesh Kumar; Sah, Kiran Kumari (International Journal of Humanities, Education, and Social Sciences, 2024)
In today's rapidly evolving and highly competitive business environment, organizations seek sustainable competitive advantages and enhanced performance through strategic management accounting (SMA). This comprehensive literature review explores the tools and techniques of SMA, bridging the gap between financial accounting and strategic decision-making. The study identifies and categorizes a wide range of SMA tools, including activity-based costing, balanced scorecard, value chain analysis, benchmarking, customer accounting and competitor accounting. The review highlights the significance of SMA in aligning financial and non-financial information with strategic objectives, facilitating informed decision-making, and improving organizational competitiveness and financial performance. Key findings emphasize the practical applications of SMA tools across various industries and sectors, as well as the challenges and ambiguities surrounding their impact assessment. The study also identifies gaps in the existing literature, particularly the need for more comprehensive insights into the contextual factors influencing the effectiveness of SMA tools. This review provides valuable insights for scholars, practitioners, and policymakers, offering a foundation for future research and practical guidance on leveraging SMA tools in today's dynamic business landscape.